Mutawasitoh Tahfidzul Qur'an (Mtq) Program For Learning Management At Nurul Huda Purbalingga Islamic Boarding School - Ghopur, Abdul; Imron, Imron (Prosiding University Research Colloquium, 2021)
Abdul Ghopur, Master's Degree Student at Muhammadiyyah University Magelang (UNIMMA) Central Java. This study aims to describe the learning management of the Mutawasithoh Tahfidzul Qur'an (Mutiq) Program at the Islamic Islamic Boarding School Nurul Huda Purbalingga, starting from lesson planning, learning implementation, and evaluation of learning implementation. This research method uses a qualitative descriptive approach. The object of this research is the learning management of the Mutawasithoh Tahfidzul Qur'an (Mutiq) Islamic Boarding School Nurul Huda Purbalingga. The method of data collection using interviews. The results of research on the learning management of the Mutiq Program at the Islamic Boarding School Nurul Huda Purbalingga show that; First; The lesson plan has been completed with a complete syllabus and Learning Implementation Plan and is well documented in the form of document/book one and document/book two, containing the syllabus, lesson plans, annual program and semester program. The Mutiq program for the Islamic Islamic Boarding School Nurul Huda Purbalingga is a type of religious education organized through the wustha/junior high school equivalent level education, so that the syllabus and lesson plans refer to equivalence education, plus a local curriculum content typical of pesantren, as well as extracurricular and intracurricular development programs for students. The learning plan is prepared by the Principal by involving elements of the foundation, teaching staff, managers, and has undergone many changes, following the dynamics of government policies and stakeholder requests. Second; The implementation of the teaching and learning process is carried out on Saturday - Thursday, starting at 07.00 - 13.00 WIB. The learning activity begins with an opening or greeting, the ustadz delivers the subject matter using learning media such as LCD, white board, and markers. The method of delivering material uses the lecture method, demonstration, and ends with a question and answer session. Ustadz closed the teaching and learning process by praying together and saying closing greetings. Third; Learning evaluation uses formative evaluation, which is an assessment in the form of a test that is carried out after a subject has been studied by students and summative evaluation, which is an assessment in the form of a test that is carried out after the teaching and learning process is completed within a certain period of time, namely one semester and than result for this research is good and effective.